Infant mortality in white‐faced capuchins: The impact of alpha male replacements. Issue 12 (15th November 2017) - Brasington, Lauren F.; Wikberg, Eva C.; Kawamura, Shoji; Fedigan, Linda M.; Jack, Katharine M.
Abstract : Infanticide is common in the context of alpha male replacements (AMR), particularly in groups where alpha males experience high reproductive skew and the infants are unlikely to be related to a new alpha male. We examined the relationship between the rate of infant mortality, infant age, and the occurrence and type of AMR in white‐faced capuchin monkeys ( Cebus capucinus imitator ) of the Santa Rosa population in Sector Santa Rosa, Área de Conservación Guanacaste. Specifically, we investigated how the source of the new alpha male (coresident or extragroup) and relative aggression level during AMRs influenced infant mortality in this species. Between 1986 and 2015, we recorded 221 births in five study groups. Infants present at the time of an AMR, or born within 5.5 months following an AMR (i.e., conceived prior to AMR), experienced significantly higher mortality than those born during periods of group stability. Infant age was a significant predictor of infant survival, with the probability of surviving increasing by 0.4% for each additional day older an infant was at the time of the AMR. Infant mortality rates did not differ between AMRs by coresident males and extragroup males, possibly because the degree of relatedness between infants and new alphas did not significantly differ between coresident and extragroup AMRs. Infant mortality rates did not differ significantly between aggressive AMRs and more peaceful AMRs. Our results are consistent with predictions derived from the sexual selection hypothesis (SSH) of infanticide and suggest that future studies examine the role of testosterone as an underlying proximate mechanism for the aggression leading to this behavior. We argue that the sexual selection and generalized aggression hypotheses (GAH) of infanticide are best considered as different levels of analysis rather than competing hypotheses. Abstract : Males become alpha via takeover, rank reversal, succession, waltz‐in, or fission. All modes to alpha are associated with higher infant mortality than during stable periods. Younger infants are at the highest risk during alpha male replacements.